2021
DOI: 10.1029/2021ja029234
|View full text |Cite
|
Sign up to set email alerts
|

Martian Crustal Field Influence on O+ and O2+ Escape as Measured by MAVEN

Abstract: Martian crustal magnetic fields influence the solar wind interaction with Mars in a way that is not fully understood. In some locations, crustal magnetic fields act as “mini‐magnetospheres,” shielding the planet's atmosphere, while in other locations they act as channels for enhanced energy input and particle escape. The net effect of this system is not intuitively clear, but previous modeling studies have suggested that crustal fields likely decrease global ion escape from Mars. In this study, we use data fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 76 publications
(106 reference statements)
0
18
0
Order By: Relevance
“…The distribution of the unit flow vectors on the northern and southern hemispheres of Mars shown by Lundin et al (2011) showed such asymmetry. This effect may result in the observed local increase in the heavy-ion number density above the strong crustal field areas (Dubinin et al 2019;Weber et al 2021;Fowler et al 2022). However, the variations in V r and V j above the strong crustal sources at the southern hemisphere are not obvious.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The distribution of the unit flow vectors on the northern and southern hemispheres of Mars shown by Lundin et al (2011) showed such asymmetry. This effect may result in the observed local increase in the heavy-ion number density above the strong crustal field areas (Dubinin et al 2019;Weber et al 2021;Fowler et al 2022). However, the variations in V r and V j above the strong crustal sources at the southern hemisphere are not obvious.…”
Section: Resultsmentioning
confidence: 98%
“…Although the effects of crustal fields on the plasma escape along the Martian magnetotail have been extensively studied using MHD simulations (e.g., Ma et al 2014;Fang et al 2015Fang et al , 2017, little attention has been paid to day-to-night plasma transport. However, in the presence of crustal fields, many heavy ions remain in the strong crustal field regions, instead of being transported away (Lundin et al 2011;Matta et al 2015;Dubinin et al 2019;Weber et al 2021). This effect results in the decrease of the heavy-ion number density transported from dayside to magnetotail and reduction in the heavy-ion loss.…”
Section: Discussionmentioning
confidence: 99%
“…For terrestrial planets in Solar System (dominated by non-thermal escape processes), it was shown that a weak magnetic field can intensify the escape, while the strong field is, in general, expected to be protective (Gunell et al 2018;Sakai et al 2018;Egan et al 2019;Ramstad & Barabash 2021). Further on, for the crustal magnetic field at Mars, the overall effect on the atmospheric mass loss depends on the configuration and inclination angle of the magnetic field (Weber et al 2021;Li et al 2022;Curry et al 2022).…”
Section: Magnetic Field and The Escape Of Planetary Atmospheresmentioning
confidence: 99%
“…Evidence from Mars missions have shown variations in magnetic field topology presumed to be a result of reconnection with crustal fields (Xu et al., 2020). Similarly, ionospheric composition and ion loss have been shown to vary depending on crustal field strength and location (Dubinin et al., 2020; Fang et al., 2017; Flynn et al., 2017; Fränz et al., 2006; Weber et al., 2021; Withers et al., 2019; Zhang et al., 2021). Crustal fields are thought to lead to departures from the nominal magnetic field draping that would occur for an un‐magnetized planet.…”
Section: Introductionmentioning
confidence: 99%